Causal relationship between Islamic and conventional banking instruments in Malaysia / Sariza Salleh - Salleh, Sariza (2007)
This study aims to examine whether Islamic banking is really different from conventional banking. The idea is to determine whether the Islamic investment rates are related to conventional deposit rates in six maturity-matched basis. The dependent variables are Islamic banks' and finance companies' investment rates on l, 3, 6, 9 and 12 month Mudharabah deposits and Islamic banks' and finance companies' investment rate on alwadiah savings deposits. On top of that, the independent variables are commercial banks' and finance companies' investment rate on 1, 3, 6, 9 and 12 month fixed deposits and commercial banks' and finance companies' investment rate on savings deposits. This study involves the Granger causality test on monthly series of Islamic investment rates and conventional deposit rates collected from the Monthly Statistical Bulletin published by Bank Negara Malaysia. The sampling period is from January 1997 to December 2006. The result shows that the changes in conventional deposit rates causes Islamic investment rates to change, but not vice versa. Means, the Islamic banking considers interest rates before adjusting its deposits returns.